ENHANCING STUDENT MOTIVATION THROUGH CREATIVE PORTFOLIOS AND COMPETITIONS - Aslonova Navro‘za Hoshim qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: Creative portfolios and competitions serve as effective strategies for increasing students’ motivation in art education. This article examines how the use of personal portfolios, curated collections of artworks, and participation in competitive events can stimulate engagement, foster self-expression, and develop artistic competencies. By documenting their creative progress and presenting their work in public or peer-reviewed settings, students gain confidence, take ownership of their learning, and are encouraged to refine their skills. The study highlights practical approaches for implementing portfolios and competitions to maximize student motivation, enhance creativity, and promote aesthetic judgment.